Preliminary X-ray crystallographic study of the receptor-binding domain of the D/C mosaic neurotoxin from Clostridium botulinum - Nuemket, Nipawan (International Union of Crystallography, 2010)

(untitled)
Botulinum toxin (BoNT) from Clostridium botulinum OFD05, isolated from bovine botulism, is a D/C mosaic-type BoNT. BoNTs possess binding, translocation and catalytic domains. The BoNT/OFD05 binding domain exhibits significant sequence identity to BoNT/C, which requires a single ganglioside as a binding receptor on neuronal cells, while BoNT/A and BoNT/B require two receptors for specific binding. To determine the binding mechanism of BoNT/OFD05 and its ganglioside receptors on neuronal cells, recombinant BoNT/OFD05 receptor-binding domain has been expressed, purified and crystallized. Native and SeMet-derivative crystals showed X-ray diffraction to 2.8 and 3.1 Å resolution, respectively. The crystals belonged to space group P2(1)2(1)2(1).